Impact of social influence, financial literacy, and self-control on saving behavior among micro and small enterprise owners in Uganda - Eva Mpaata; Mahadih Kyambade; Augustine Matovu; Josephine Naigwe (Cogent Psychology)
This study examines the moderating role of self‑control in the relationship between financial literacy, social influence, and savings behavior among Micro and Small Enterprise (MSE) owners in Kampala, Uganda. The study aims to establish whether self‑control influences the association between financial literacy and savings behavior, as well as between social influence and savings behavior. A cross‑sectional research design was employed, targeting MSE owners officially registered with Uganda Bureau of Statistics (UBOS) and Kampala Capital City Authority (KCCA). A total of 373 responses were analyzed using PROCESS Macro Model 3.2. The findings indicate that financial literacy and social influence significantly impact savings behavior. self‑control significantly moderates the relationship between financial literacy and savings behavior, as well as between social influence and savings behavior. Individuals with higher self‑control exhibited stronger savings behavior than those with lower self‑control, even as financial literacy and social influence improved. Findings highlight that financial literacy, social influence, and self‑control play significant roles in shaping savings behavior among MSE owners in Kampala. Social networks and financial knowledge contribute to better financial decision‑making, while self‑control moderates these relationships. The findings suggest that policymakers and financial educators should integrate self‑control training into financial literacy programs to enhance savings behavior among MSE owners.